Potential Use Of Virtual Environments In Design Education - Sagun, Aysu (The Turkish Online Journal of Design Art and Communication, 2011)
This paper explores the potential use of Virtual Environments (VE) in design education. Recently, the way the designers form their mental concepts, develop and test their design is enhanced with the new computer technologies. Computer generated VE has a great potential to be used in the design process and collaborative studies because they enable manipulation of simulated products as well as interaction of people with each other and the simulated space for communication and collaboration. Therefore, 3D virtual worlds constructed on computer enable a better understanding of the design ideas and solutions. VE can also enhance the education of next generation designers enabling students and instructors to check designs solutions and failures rapidly. It can also provide students a medium for discussions with their instructors, other students or design experts. In this paper, properties of VEs and two popular VE modelling languages, Virtual Reality Modelling Language (VRML) and Extensible 3D (X3D), are explained. The nature of design education is introduced and the reasons why VE is a convenient tool for design education is discussed, pointing out the short comes that need developments in future.
Keywords: Design education; Dizayn eğitimi; collaboration; İşbirliği; virtual environments; sanal ortamlar; Virtual Reality Modelling Language; Sanal Gerçeklik Modelleme Dili; Extensible 3D Graphics; Genişletilebilir 3D Grafik